Preparation process of high-performance fracturing fluid emulsion type thickening agent

By introducing dynamic crosslinking agents and temperature-sensitive monomers into the fracturing liquid thickening agent preparation process, a reversible crosslinking network and intelligent response characteristics are formed, which solves the problem of insufficient stability and adaptability of thickening agents in high temperature, high shear and high salt environments, and achieves high performance performance of thickening agents.

CN119591782APending Publication Date: 2025-03-11西安峻邦生物科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411779238.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing fracturing fluid thickening agents show insufficient stability and fast performance decay in high temperature, high shear and high salt environments.

Method used

A high-performance fracturing liquid emulsion-type thickening agent preparation process is adopted. By mixing the oil phase with the emulsifier, the aqueous phase is prepared and the reverse phase emulsion is formed by high-speed shearing. Then the polymerization reaction is carried out under nitrogen protection, and a dynamic crosslinking agent is added to form a dynamic crosslinking network structure after polymerization is formed. Finally, the emulsion-type thickening agent is obtained through separation, purification and homogenization treatment.

Benefits of technology

It significantly improves the viscosity recovery rate and structural stability of the thickener in high shear environment, ensuring excellent performance of the thickener under high temperature, high salt and high shear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591782A_ABST
    Figure CN119591782A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thickening agents, and discloses a preparation process of a high-performance fracturing fluid emulsion type thickening agent. The preparation method comprises the following steps: S1, uniformly mixing 30-50% of oil phase and 50-70% of emulsifier; s2, preparing a water phase: dissolving a monomer and a cross-linking agent in water, and adjusting the pH to prepare the water phase; s3, emulsifying: dropwise adding the water phase into the oil phase, and performing high-speed shearing to form an inverse emulsion; and S4, polymerization reaction: adding an initiator under the protection of nitrogen, and carrying out polymerization reaction at 50-70 DEG C. By introducing the dynamic cross-linking agent, a reversible cross-linked network is formed in the molecular structure of the thickening agent. When the molecular chain of the thickening agent is broken under the action of high shearing force, the dynamic cross-linked structure can quickly reconstruct a molecular network, and the viscosity recovery rate of the thickening agent after shearing is ensured. And compared with the problem of low recovery rate caused by incapability of repairing broken molecules in the prior art, the adaptive capacity of the thickening agent in a high-shear environment is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thickeners, and in particular to a preparation process of a high-performance fracturing fluid emulsion thickener. Background Art

[0002] In the process of oil and gas field exploitation, fracturing fluid is a key engineering fluid, and its performance directly affects the effect and cost of fracturing operations. As the core component of fracturing fluid, thickener is mainly used to enhance the viscosity of fracturing fluid and provide sufficient sand carrying capacity to achieve effective filling of cracks. However, existing fracturing fluid thickeners often show insufficient performance in high temperature, high shear and high salt environments, which is specifically reflected in the following aspects.

[0003] The currently commonly used thickeners are prone to molecular chain breakage under high shear conditions, resulting in a rapid decrease in viscosity, and the broken molecular chains cannot repair themselves, making it difficult to restore viscosity. This performance deficiency seriously affects the sand carrying capacity and effectiveness of fracturing fluids in complex downhole environments, increasing operational risks and costs.

[0004] The high temperature conditions in underground working environments place extremely high demands on the molecular structure stability of thickeners. However, existing thickeners are prone to degradation or molecular chain entanglement under high temperature conditions, resulting in a decrease in viscosity, which cannot meet the use requirements of deep and ultra-deep formations.

[0005] The emulsions formed during the preparation of many thickeners are prone to phase separation during storage and use, and the emulsion particle size distribution is uneven and the structural stability is poor. Emulsion phase separation not only reduces the efficiency of the thickener, but also may affect the overall performance of the fracturing fluid.

[0006] Therefore, the present invention provides a process for preparing a high-performance fracturing fluid emulsion thickener. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a process for preparing a high-performance fracturing fluid emulsion thickener, which solves the problems of insufficient stability and rapid performance degradation of the existing thickeners in complex downhole environments such as high temperature, high shear, and high salt.

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions: A process for preparing a high-performance fracturing fluid emulsion thickener comprises the following steps;

[0009] S1. Evenly mix 30% to 50% of the oil phase and 50% to 70% of the emulsifier;

[0010] S2, preparing an aqueous phase: dissolving the monomer and the cross-linking agent in water, and adjusting the pH to prepare an aqueous phase;

[0011] S3, emulsification: adding the water phase dropwise into the oil phase to form an inverse emulsion through high-speed shearing;

[0012] S4, polymerization reaction: adding initiator under nitrogen protection, and carrying out polymerization reaction at 50°C to 70°C;

[0013] S5, cross-linking treatment: adding a dynamic cross-linking agent in the late stage of polymerization to form a dynamic cross-linking network structure;

[0014] S6. Post-processing: Through separation, purification and homogenization, an emulsion thickener product is obtained.

[0015] Preferably, the oil phase in step S1 includes but is not limited to mineral oil and vegetable oil.

[0016] Preferably, the emulsifier in step S1 includes a bifunctional emulsifier and a temperature-sensitive emulsifier;

[0017] The bifunctional emulsifier is aminopropyl polydimethylsiloxane, which accounts for 70% to 80% of the total mass of the emulsifier;

[0018] The temperature-sensitive emulsifier is a poly-N-isopropylacrylamide modified surfactant, which accounts for 20% to 30% of the total mass of the emulsifier;

[0019] The bifunctional emulsifier accounts for 70% to 80% of the total mass of the emulsifier;

[0020] The temperature-sensitive emulsifier accounts for 20% to 30% of the total mass of the emulsifier.

[0021] Preferably, the preparation of the aqueous phase in step S2 specifically includes:

[0022] S2.1, dissolve the monomer in deionized water, the total monomer concentration is 20% to 25%;

[0023] S2.2, adding 0.05% to 0.1% of N,N'-methylenebisacrylamide as a basic crosslinking agent, and adding 0.05% to 0.2% of a thiol-containing compound as a dynamic crosslinking agent;

[0024] S2.3, after uniform mixing by stirring, adjust the pH value of the solution to 7.5-8 using a pH adjuster;

[0025] S2.4. Use a homogenizer to stir at a speed of 3000RPM to 5000RPM for 3min to 5min to form a uniform aqueous solution.

[0026] Preferably, the monomers include: 50% to 60% acrylamide, 15% to 20% cationic monomer, 5% to 10% hydrophobic monomer and 10% to 15% thermosensitive monomer.

[0027] Preferably, the emulsification in step S3 specifically includes:

[0028] S3.1, add the aqueous phase solution to the oil phase dropwise at a constant rate to ensure a uniform oil-water ratio and control the drop rate to avoid agglomeration of the aqueous phase;

[0029] S3.2, under the action of high-speed shearing equipment, at a speed of 3000RPM to 5000RPM, the time is controlled within 15min to 30min, so that the particle size of the formed emulsion is uniform and stable, and the particle size range is controlled within 10μm to 50μm;

[0030] S3.3. During the emulsification process, maintain the system temperature at 20℃~30℃ to prevent the emulsifier performance from being affected by temperature fluctuations and ensure the stability of the emulsion.

[0031] Preferably, the polymerization reaction in step S4 specifically includes:

[0032] S4.1, initial polymerization stage: the prepared inverse emulsion is placed in a polymerization reactor, nitrogen is introduced to remove oxygen, the gas flow rate is controlled at 0.5L / min to 1.0L / min, the ventilation time is 10min to 30min, and then the temperature is raised to 50℃ to 55℃;

[0033] S4.2, add redox initiator, the oxidant is ammonium persulfate, the reductant is sodium bisulfite, the mass ratio of oxidant to reductant is 1:1.2, and the amount of initiator is 0.5% to 1% of the total mass of the monomer

[0034] S4.3, the initial polymerization temperature is controlled at 50℃~55℃, the reaction time is 1h~2h, after the emulsion gradually thickens, slowly raise the temperature to 60℃~70℃, and keep the reaction time for 2h~4h until the viscosity reaches the target value;

[0035] S4.4, after the reaction has been going on for 2h to 3h, add the nanocapsule-coated initiator, the capsule particle size is 200nm to 500nm, and the controlled release time is 1h to 2h, to optimize the monomer polymerization rate and molecular weight distribution;

[0036] S4.5. After the reaction is completed, the system is naturally cooled to room temperature, and stirring is stopped to obtain a polymer emulsion thickener.

[0037] Preferably, the cross-linking treatment in step S5 specifically includes:

[0038] S5.1. After the polymerization reaction has been carried out for 3 to 4 hours, the dynamic crosslinking agent is dissolved in deionized water, and the concentration of the solution is controlled at 0.5% to 1.5%;

[0039] S5.2, slowly adding the dynamic crosslinking agent solution into the polymerization system, the dynamic crosslinking agent accounting for 0.05% to 0.2% of the total weight of the monomer;

[0040] S5.3. After the dynamic cross-linking agent and the polymerization system are uniformly mixed, stirring is continued for 30 min to 60 min, the stirring speed is controlled at 20 rpm to 500 rpm, and the reaction temperature is maintained at 50°C to 70°C.

[0041] Preferably, the dynamic cross-linking agent includes but is not limited to thiol-containing compounds and disulfide compounds.

[0042] Preferably, the post-processing in step S6 specifically includes:

[0043] S6.1, using centrifugal separation, the centrifugal speed is 3000RPM ~ 5000RPM, the time is 10min ~ 30min, to remove unreacted monomers and impurities;

[0044] S6.2, washing the emulsion 2 to 4 times with deionized water, with the ratio of washing volume to emulsion mass being 2:1, to ensure the removal of water-soluble impurities, and purifying the emulsion by a microfiltration device with a filtration pore size of 1 μm to 5 μm to control the particle size distribution of the emulsion;

[0045] S6.3, use high-pressure homogenization equipment for homogenization treatment, the homogenization pressure is controlled at 20MPa ~ 30MPa, the homogenization time is 10min ~ 20min, ensure that the uniformity of the emulsion particle size is within the range of 10μm ~ 50μm, add antioxidant to stabilize the product, and the amount of antioxidant added is 0.1% ~ 0.3% of the total mass of the emulsion;

[0046] S6.4. Adjust the treated emulsion to a solid content of 30% to 50%, and finally store the emulsion thickener in a sealed container and keep it at 15°C to 30°C away from light.

[0047] The present invention provides a process for preparing a high-performance fracturing fluid emulsion thickener. It has the following beneficial effects:

[0048] 1. The present invention forms a reversible crosslinking network in the thickener molecular structure by introducing a dynamic crosslinking agent. When the thickener molecular chain breaks under high shear force, the dynamic crosslinking structure can quickly rebuild the molecular network to ensure the viscosity recovery rate of the thickener after shear. Compared with the problem of low recovery rate due to the inability to repair molecular breaks in the prior art, the adaptability of the thickener in a high shear environment is significantly improved.

[0049] 2. The present invention uses a temperature-sensitive monomer to give the thickener an intelligent response characteristic, so that it can adjust the molecular chain configuration according to the changes in the underground high-temperature environment, thereby maintaining the integrity of the emulsion structure and the viscosity stability under extreme temperatures. This high-temperature adaptability solves the problem that traditional thickeners are easily degraded and their performance rapidly decreases under high temperature conditions, ensuring the long-term effectiveness of the thickener.

[0050] 3. The present invention optimizes the ratio of cationic monomers and temperature-sensitive monomers in the monomer system, and the thickener of the present invention exhibits excellent salt resistance in high-mineralization formation water. The thickener can maintain a stable molecular chain structure and viscosity characteristics in a high-salt environment, is not interfered by ions, adapts to the needs of different geological conditions, and provides a wider range of applicability for fracturing fluids. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The present invention is a flow chart of the preparation process. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Please refer to the attached Figure 1 , the embodiment of the present invention provides a process for preparing a high-performance fracturing fluid emulsion thickener, comprising the following steps;

[0054] S1. Evenly mix 30% to 50% of the oil phase and 50% to 70% of the emulsifier;

[0055] S2, preparing an aqueous phase: dissolving the monomer and the cross-linking agent in water, and adjusting the pH to prepare an aqueous phase;

[0056] S3, emulsification: adding the water phase dropwise into the oil phase to form an inverse emulsion through high-speed shearing;

[0057] S4, polymerization reaction: adding initiator under nitrogen protection, and carrying out polymerization reaction at 50°C to 70°C;

[0058] S5, cross-linking treatment: adding a dynamic cross-linking agent in the late stage of polymerization to form a dynamic cross-linking network structure;

[0059] S6, post-processing: obtaining an emulsion thickener product through separation, purification and homogenization;

[0060] Specifically, through the introduction of dynamic cross-linking agents, the synergistic effect of bifunctional emulsifiers and thermosensitive emulsifiers, and the optimization of nanocapsule controlled release initiation technology, an emulsion-type thickener with high viscosity, strong shear recovery and excellent salt resistance is constructed. The process design fully considers the interaction between the formula ratio, emulsification process and polymerization parameters to ensure the performance stability of the thickener under complex geological conditions;

[0061] Oil phase mixed with emulsifier

[0062] Oil phase selection:

[0063] The oil phase includes mineral oil or vegetable oil, which serves as the continuous phase of the emulsion and has good emulsifying properties and environmental compatibility.

[0064] The oil phase accounts for 30% to 50% of the total mass of the emulsion.

[0065] Emulsifier configuration:

[0066] The emulsifier is composed of aminopropyl polydimethylsiloxane as a bifunctional emulsifier and poly N-isopropylacrylamide modified surfactant as a temperature-sensitive emulsifier.

[0067] The bifunctional emulsifier accounts for 70% to 80% of the total mass of the emulsifier, and can simultaneously stabilize the emulsion and enhance the anchoring effect of the thickener molecular chain segment.

[0068] Thermosensitive emulsifiers account for 20% to 30% of the total mass of the emulsifiers, and they enhance the stability of the emulsion by changing the molecular configuration under high temperature conditions.

[0069] Emulsifier accounts for 50% to 70% of the oil phase mass

[0070] Add the emulsifier to the oil phase and stir for 15 to 30 minutes to make the emulsifier evenly distributed in the oil phase;

[0071] Aqueous phase preparation;

[0072] Monomer dissolution:

[0073] The monomers include 50% to 60% of acrylamide, 15% to 20% of cationic monomers, 5% to 10% of hydrophobic monomers and 10% to 15% of thermosensitive monomers.

[0074] The total monomer concentration is 20% to 25%, and is dissolved in deionized water.

[0075] Crosslinker addition:

[0076] Basic cross-linking agent: N, N'-methylenebisacrylamide is used in an amount of 0.05% to 0.1% of the total weight of the monomers, and is used to construct an initial three-dimensional network structure.

[0077] Dynamic crosslinking agent: containing mercapto compounds, the dosage is 0.05% to 0.2% of the total weight of the monomer, which gives the thickener shear recovery properties;

[0078] pH adjustment:

[0079] Sodium hydroxide was used to adjust the pH of the aqueous phase to 7.5-8.0 to ensure a suitable acid-base environment for the polymerization reaction.

[0080] Homogenization:

[0081] Use a homogenizer to stir at a speed of 3000RPM to 5000RPM for 35 minutes to evenly disperse the water phase; emulsify

[0082] Add water phase dropwise:

[0083] The aqueous phase solution was added dropwise to the oil phase at a constant rate to ensure a uniform oil-water ratio and avoid agglomeration of the aqueous phase;

[0084] The dropping speed is controlled at 5mL / min~10mL / min, and the emulsification time is 15min~30min;

[0085] High-speed shear emulsification:

[0086] Use high-speed shearing equipment at 3000RPM to 5000RPM, shear emulsification at 20°C to 30°C, and control the emulsion particle size within the range of 10μm to 50μm.

[0087] The particle size is detected in real time by a laser particle size analyzer to ensure uniform distribution of the emulsion particle size;

[0088] Polymerization

[0089] Initial aggregation:

[0090] The emulsified system was placed in a reaction kettle and nitrogen was introduced at a flow rate of 0.5 L / min to 1.0 L / min for 10 min to 30 min to remove oxygen.

[0091] The temperature is raised to 50°C to 55°C, and a redox initiator is added. The oxidizing agent is ammonium persulfate, and the reducing agent is sodium bisulfite. The mass ratio of the two is 1:1.2, and the total amount is 0.5% to 1% of the total mass of the monomer.

[0092] Controlled Release Triggering:

[0093] After the reaction is carried out for 1 hour to 2 hours, a nanocapsule-coated initiator with a particle size of 200 nm to 500 nm is added, and the controlled release time is 1 hour to 2 hours.

[0094] The controlled-release initiator optimizes the polymerization rate of the monomers and makes the molecular weight distribution of the final product more uniform.

[0095] Reaction completion:

[0096] After the emulsion thickens, slowly heat it to 60°C to 70°C and react for 2h to 4h until the viscosity reaches the target value;

[0097] Cross-linking treatment

[0098] Dynamic crosslinker dissolution:

[0099] After the reaction has been carried out for 3 to 4 hours, the dynamic cross-linking agent is dissolved in deionized water at a concentration of 0.5% to 1.5%;

[0100] Add and Mix:

[0101] Slowly add the dynamic crosslinking agent solution into the polymerization system, the amount of the dynamic crosslinking agent is 0.05% to 0.2% of the total weight of the monomer;

[0102] Continue stirring for 30 min to 60 min, control the stirring speed at 20 RPM to 500 RPM, and maintain the temperature at 50°C to 70°C;

[0103] Cross-linking network formation:

[0104] The mercapto compounds react with the thickener molecular segments to form reversible SS cross-linking bonds, giving the thickener excellent shear recovery properties;

[0105] Post-processing;

[0106] Separation and purification:

[0107] Use a centrifuge at 3000RP~M5000RPM for 10min~30min to separate unreacted monomers and impurities.

[0108] The emulsion was washed with deionized water for 2 to 4 times, with the mass ratio of washing liquid to emulsion being 2:1.

[0109] Homogenization and particle size control:

[0110] The emulsion is treated with a high-pressure homogenization device at a pressure of 20 MPa to 30 MPa to make the particle size distribution uniform in the range of 10 μm to 50 μm.

[0111] Antioxidant treatment:

[0112] Add antioxidants such as vitamin E in an amount of 0.1% to 0.3% of the total mass of the emulsion to extend the storage time of the product.

[0113] Adjustment and storage:

[0114] Adjust the solid content of the emulsion to 30% to 50%, store the product in a sealed container, and keep it away from light at 15℃ to 30℃;

[0115] The process achieves excellent performance of the thickener under complex formation conditions such as high temperature, high salt and high shear. The process uses mineral oil or vegetable oil as the oil phase, combines a bifunctional emulsifier with a thermosensitive emulsifier to form a stable inverse emulsion system, and introduces a thiol-containing compound as a dynamic cross-linking agent to synergize with the basic cross-linking agent to construct a three-dimensional network structure with reversible cross-linking ability, thereby greatly improving the viscosity recovery and structural stability of the thickener.

[0116] Embodiment 1:

[0117] Oil phase preparation;

[0118] Weigh 40% of low-viscosity mineral oil as the oil phase matrix, add aminopropyl polydimethylsiloxane, accounting for 75% of the total mass of the emulsifier, and poly (N-isopropylacrylamide) modified surfactant, accounting for 25% of the total mass of the emulsifier, into the mineral oil, stir with a magnetic stirrer at a speed of 500 rpm for 15 minutes to ensure that the emulsifier is completely dispersed in the oil phase;

[0119] Aqueous phase preparation;

[0120] Acrylamide, accounting for 55% of the total monomer mass, cationic monomer, 18%, hydrophobic monomer, 7% and thermosensitive monomer, 15% were added to deionized water in sequence, and the total monomer concentration was 20%. N,N'-methylenebisacrylamide, accounting for 0.08% of the total monomer mass, and 0.1% of thiol-containing compound were added as a dynamic crosslinker. The pH value of the aqueous phase was adjusted to 8.0 with a pH adjuster, and a homogenizer was used to stir at 3000 rpm for 3 minutes to form a uniform aqueous phase solution.

[0121] Emulsification process;

[0122] The water phase was added dropwise to the oil phase at a constant rate, the dropping speed was controlled to prevent agglomeration, and the shearing device speed was kept at 4000 rpm, and the emulsification time was 20 min to form a stable inverse emulsion. The particle size of the emulsion was measured, and the distribution range was 25 μm.

[0123] Polymerization reaction;

[0124] Under nitrogen protection, the emulsion was transferred into a reactor, and nitrogen was introduced for 15 minutes to remove oxygen. After the emulsion was heated to 50°C, redox initiators ammonium persulfate and sodium bisulfite were added in a mass ratio of 1:1.2, and the total amount was 0.8% of the total mass of the monomers. After reacting for 1 hour, nanocapsule-coated initiator with a particle size of 300 nm was added, and the controlled release time was 1.5 hours. The temperature was gradually raised to 65°C, and the reaction was continued for 3 hours. The viscosity gradually increased until the target value was reached.

[0125] Post-processing;

[0126] The unreacted components were separated by centrifugation at a speed of 4000 rpm for 20 min, washed with deionized water for 3 times, and purified by a microfiltration device with a pore size of 2 μm. Finally, a high-pressure homogenization device was used for homogenization at a pressure of 25 MPa for 15 min to adjust the uniformity of the emulsion particle size, and the solid content of the emulsion was adjusted to 40%, and stored in a sealed container at 20°C.

[0127] Summarize:

[0128] This embodiment achieves excellent viscosity retention and shear recovery ability under high temperature and high salt conditions through the synergistic effect of the dynamic cross-linking agent and the temperature-sensitive monomer, and the emulsion has uniform particle size and stable performance.

[0129] Embodiment 2:

[0130] Oil phase preparation;

[0131] Weigh 20% of mineral oil as the oil phase, add the bifunctional emulsifier aminopropyl polydimethylsiloxane, accounting for 60% of the total mass of the emulsifier, and the thermosensitive emulsifier PNIPAM modified surfactant, accounting for 15% of the total mass of the emulsifier, into the mineral oil, and stir with a magnetic stirrer at a speed of 400 rpm for 10 minutes.

[0132] Aqueous phase preparation;

[0133] Add acrylamide to deionized water, accounting for 40% of the total monomer mass, 10% of cationic monomer, 3% of hydrophobic monomer, and 8% of thermosensitive monomer, with a total monomer concentration of 15%. Add 0.03% of basic crosslinker and 0.05% of dynamic crosslinker, adjust the pH value to 7.5, and use a homogenizer to stir at 2000 rpm for 3 minutes.

[0134] Emulsification process;

[0135] Add the water phase dropwise into the oil phase, emulsification speed 2000rpm, time 10min. The emulsion particle size distribution range is 10μm;

[0136] Polymerization reaction;

[0137] The initial polymerization temperature was 45°C, and a redox initiator was added in an amount of 0.5% of the total mass of the monomers. After reacting for 1 hour, the temperature was raised to 60°C and the reaction was continued for 2 hours;

[0138] Post-processing;

[0139] The centrifugal speed was 3000 rpm, the time was 10 min, the homogenization pressure was 15 MPa, and the final solid content was adjusted to 30%;

[0140] Summarize:

[0141] In this embodiment, due to the low content of dynamic crosslinking agent and temperature-sensitive monomer, the emulsion particle size is wide, the viscosity recovery is poor, and the weather resistance is insufficient.

[0142] Embodiment 3:

[0143] Oil phase preparation;

[0144] Mineral oil accounts for 60% of the total mass of the emulsion, while bifunctional emulsifier and thermosensitive emulsifier account for 85% and 30% of the total mass of the emulsifier, respectively;

[0145] Aqueous phase preparation;

[0146] The total monomer concentration is 25%, including 65% acrylamide, 25% cationic monomer, 15% hydrophobic monomer, 20% thermosensitive monomer, 0.12% basic crosslinker and 0.3% dynamic crosslinker, respectively;

[0147] Emulsification process;

[0148] The emulsification speed was 5000 rpm, the emulsification time was 30 min, and the emulsion particle size distribution was 30 μm;

[0149] Polymerization reaction;

[0150] Initial temperature 55°C, raised to 70°C, total reaction time 5h;

[0151] Post-processing;

[0152] Centrifugal speed 5000rpm, homogenization pressure 30MPa, time 20min;

[0153] Summarize:

[0154] High concentrations of dynamic crosslinkers and temperature-sensitive monomers significantly increase the viscosity and shear recovery of the thickener, but increase the preparation cost.

[0155] Embodiment 4;

[0156] Oil phase preparation;

[0157] Oil phase ratio: Weigh mineral oil to account for 60% of the total mass of the emulsion.

[0158] Emulsifier ratio: bifunctional emulsifier aminopropyl polydimethylsiloxane, accounting for 85% of the total mass of the emulsifier, and thermosensitive emulsifier PNIPAM modified surfactant, accounting for 30% of the total mass of the emulsifier, are mixed into the oil phase;

[0159] Stirring parameters: stirring speed 400 rpm, time 15 min, until the emulsifier is completely dispersed in the oil phase and the oil phase is in a uniform state;

[0160] Aqueous phase preparation;

[0161] Monomer ratio: acrylamide, accounting for 65% of the total monomer mass, cationic monomer 25%, hydrophobic monomer 15% and thermosensitive monomer 20%;

[0162] Cross-linking agent addition: adding the basic cross-linking agent N,N'-methylenebisacrylamide, accounting for 0.12% of the total weight of the monomer, and the dynamic cross-linking agent containing thiol compound, accounting for 0.3% of the total weight of the monomer;

[0163] Dissolution and homogenization: The total monomer concentration is 25%, dissolved in deionized water, the pH value is adjusted to 8.0, and stirred at 2000 rpm for 3 min using a homogenizer;

[0164] Emulsification process;

[0165] Emulsification operation: add the water phase to the oil phase at a constant rate, control the dripping speed to prevent agglomeration. Use high-speed shearing equipment, control the shearing speed to 2000rpm, and the emulsification time to 15min;

[0166] Particle size distribution: The particle size range of the inverse emulsion after emulsification is 35μm;

[0167] Polymerization reaction;

[0168] Initial polymerization stage: the emulsion was transferred into a reactor and nitrogen was introduced for deoxygenation. The ventilation time was 15 min and the starting temperature of the polymerization reaction was 45°C.

[0169] Initiator addition: Add redox initiator, the total mass is 0.8% of the total mass of monomers, polymerization time is 1h;

[0170] Heating polymerization: slowly raise the temperature to 60°C, total reaction time 3h;

[0171] Post-processing;

[0172] Separation and purification: centrifugation was used at 3000 rpm for 10 min. The mixture was washed twice with deionized water and the particle size uniformity of the emulsion was adjusted using a microfiltration device with a pore size of 5 μm.

[0173] Homogenization treatment: homogenization pressure 15MPa, homogenization time 10min, final adjustment of emulsion solid content to 35%;

[0174] Summarize:

[0175] This embodiment has lower emulsification parameters and a wider range of emulsion particle sizes, and its weather resistance and stability are lower than those of Example 1, but the high content of dynamic crosslinking agent and temperature-sensitive monomer makes the viscosity retention of the thickener under high temperature conditions still superior to the prior art. The particle size uniformity and shear recovery ability are poor.

[0176] Embodiment 5;

[0177] Oil phase preparation

[0178] Oil phase ratio: weigh mineral oil to account for 20% of the total mass of the emulsion;

[0179] Emulsifier ratio: bifunctional emulsifier aminopropyl polydimethylsiloxane, accounting for 60% of the total mass of the emulsifier, and thermosensitive emulsifier PNIPAM modified surfactant, accounting for 15% of the total mass of the emulsifier, are mixed into the oil phase;

[0180] Stirring parameters: stirring speed 500 rpm, time 20 min;

[0181] Aqueous phase preparation;

[0182] Monomer ratio: acrylamide, accounting for 40% of the total monomer mass, cationic monomer 10%, hydrophobic monomer 3% and thermosensitive monomer 8%.

[0183] Cross-linking agent addition: add basic cross-linking agent, accounting for 0.03% of the total weight of the monomer, and dynamic cross-linking agent containing thiol compounds, accounting for 0.05% of the total weight of the monomer,

[0184] Dissolution and homogenization: The total monomer concentration is 15%, dissolved in deionized water, the pH value is adjusted to 7.5, and stirred at 4000 rpm for 5 min using a homogenizer;

[0185] Emulsification process;

[0186] Emulsification operation: add the water phase to the oil phase at a constant rate, use a high-speed shearing device, control the shear speed to 5000 rpm, and emulsification time to 30 min.

[0187] Particle size distribution: The particle size range of the inverse emulsion after emulsification is 25μm.

[0188] Polymerization reaction;

[0189] Initial polymerization stage: the emulsion was transferred into a reactor and nitrogen was introduced for deoxygenation. The ventilation time was 20 min and the starting temperature of the polymerization reaction was 55°C.

[0190] Initiator addition: Add redox initiator, the total mass of which is 0.5% of the total mass of monomers, and the polymerization time is 2 h.

[0191] Temperature polymerization: slowly increase the temperature to 70°C, with a total reaction time of 5 hours.

[0192] Post-processing;

[0193] Separation and purification: centrifugation was used at a speed of 5000 rpm for 20 min, and washing was performed 4 times with deionized water.

[0194] Homogenization treatment: homogenization pressure 30MPa, homogenization time 20min, final adjustment of emulsion solid content to 40%;

[0195] Summarize:

[0196] Due to the low content of dynamic crosslinking agent and temperature-sensitive monomer, the viscosity retention and intelligent response ability of this embodiment are poor, but due to the improvement of emulsification parameters and post-processing conditions, the particle size distribution of the emulsion is more uniform and the phase separation time is extended. High process parameters improve stability, but the lack of ingredients makes the overall performance still weaker than that of Example 1.

[0197] Example data table

[0198] Table 1:

[0199] index Example 1 Example 2 Example 3 Example 4 Example 5 Shear loss rate (%) 20 35 18 25 30 Viscosity recovery rate after shear (%) 90 60 95 75 65 Viscosity change rate (%) 8.3 20 7.5 12.5 15 Particle size range (μm) 25 10 30 35 25 Phase separation time (h) >48 <24 >72 24 >36

[0200] Shear loss rate and recovery rate

[0201] In Example 1, within the scope of innovative ingredients and process parameters, the shear loss rate is low and the recovery rate is high, showing excellent anti-shear performance.

[0202] Example 3 has the highest recovery rate and the lowest loss rate because the innovative ingredients are higher than the range value, but the preparation cost is relatively high.

[0203] The shear performance of Examples 2 and 5 is poor due to insufficient innovative ingredients.

[0204] Comparative experiment 1;

[0205] Comparative Example 1;

[0206] Oil phase: mineral oil accounts for 40% of the total mass of the emulsion;

[0207] Emulsifier: bifunctional emulsifier (aminopropyl polydimethylsiloxane, accounting for 75% of the total mass of the emulsifier) ​​and thermosensitive emulsifier (PNIPAM modified surfactant, accounting for 25% of the total mass of the emulsifier);

[0208] Monomer system:

[0209] Acrylamide: 55%;

[0210] Cationic monomer: 18%;

[0211] Hydrophobic monomer: 7%;

[0212] Thermosensitive monomer: 15%;

[0213] Cross-linking agent: only basic cross-linking agent (N,N'-methylenebisacrylamide, accounting for 0.08% of the total monomer mass) was added, and no dynamic cross-linking agent was added;

[0214] Emulsification process: emulsification speed 4000rpm, time 20min, emulsion particle size distribution range 40μm;

[0215] Polymerization reaction: initial polymerization temperature 50°C, heating to 65°C, total reaction time 4h;

[0216] Post-treatment: homogenization pressure 25MPa, time 15min;

[0217] Comparative experimental procedures;

[0218] Shear recovery test: Place the sample in a rotational viscometer and measure the viscosity recovery rate after shearing at a shear rate of 500s-1 for 10 minutes.

[0219] Weathering performance test: After the sample is stored in a 120°C environment for 48 hours, the viscosity change rate is measured;

[0220] Emulsion stability test: observe the phase separation of the emulsion and record the phase separation time;

[0221] Compare the results;

[0222] index Example 1 Comparative Example 1 Viscosity loss rate (%) 20 40 Viscosity recovery rate after shear (%) 90 60 Viscosity change rate (%) 8.3 15 Phase separation time (h) >48 <24

[0223] Result analysis;

[0224] Effects of missing dynamic cross-linker:

[0225] Dynamic crosslinkers introduce reversible crosslinking structures into thickener molecular chains, which can quickly repair the molecular chain structure after shear force, significantly improving viscosity recovery and weather resistance. Existing technologies that lack dynamic crosslinkers have poor shear recovery and a viscosity loss rate of up to 40%, making them unsuitable for high shear downhole environments.

[0226] Differences in emulsion stability:

[0227] Dynamic cross-linking agents can also enhance the stability of the internal structure of the emulsion, significantly prolonging its phase separation time under high-temperature storage conditions.

[0228] Comparative experiment 2;

[0229] Comparative Example 2:

[0230] Oil phase: Mineral oil accounts for 40% of the total mass of the emulsion.

[0231] Emulsifier: Bifunctional emulsifier (aminopropyl polydimethylsiloxane, accounting for 75% of the total mass of the emulsifier).

[0232] Monomer system:

[0233] Acrylamide: 70%;

[0234] Cationic monomer: 20%;

[0235] Hydrophobic monomer: 10%;

[0236] No temperature-sensitive monomer PNIPAM;

[0237] Cross-linking agent: basic cross-linking agent (N,N'-methylenebisacrylamide, accounting for 0.08% of the total monomer mass) and dynamic cross-linking agent (containing thiol compound, accounting for 0.1% of the total monomer mass);

[0238] Emulsification process: emulsification speed 4000rpm, time 20min, emulsion particle size distribution range 40μm;

[0239] Polymerization reaction: initial polymerization temperature 50°C, heating to 65°C, total reaction time 4h;

[0240] Post-treatment: homogenization pressure 25MPa, time 15min;

[0241] Comparative experimental process

[0242] Intelligent responsiveness test: Test the viscosity change under different salt concentrations of 5%, 10%, 20% NaCl and pH range of 5-9, and record its intelligent response performance.

[0243] Weathering performance test: After the sample is stored in a high temperature environment of 150°C for 48 hours, the viscosity change rate is measured.

[0244] Emulsion stability test: observe the phase separation of the emulsion and record the phase separation time;

[0245] Compare the results;

[0246]

[0247]

[0248] Result analysis;

[0249] Effects of loss of thermosensitive monomers:

[0250] Thermosensitive monomer PNIPAM gives the thickener the ability to respond intelligently to temperature, salt concentration and pH conditions. Existing technologies without PNIPAM cannot maintain good viscosity performance under different conditions, especially in high-salt environments, where the viscosity drops significantly;

[0251] Weatherability and emulsion stability:

[0252] The ability of thermosensitive monomers to regulate the forces acting on emulsion molecules can also improve weather resistance and emulsion stability. Under high temperature storage conditions, the technical solution of the present invention exhibits better viscosity retention and phase separation stability;

[0253] Summarize;

[0254] Shear loss rate

[0255] The technical solution of the present invention (Example 1): The shear loss rate is 20%, showing excellent shear resistance. This is because the dynamic crosslinking agent can release stress under the action of shear force and then restore the molecular chain network through reversible crosslinking.

[0256] Comparative Example 1 (without dynamic crosslinking agent): The shear loss rate is 40%. Due to the lack of dynamic crosslinking structure, the molecular chain breakage under the shear force is irreversible.

[0257] Comparative Example 2 (without temperature-sensitive monomer): The shear loss rate is 25%, which is slightly better than Comparative Example 1, but due to the lack of temperature-sensitive regulation, the network flexibility and recovery are poor;

[0258] Viscosity recovery rate after shear

[0259] Technical solution of the present invention (Example 1): The viscosity recovery rate after shearing is 90%, the dynamic cross-linking agent provides reversible cross-linking ability, and the viscosity can be quickly recovered.

[0260] Comparative Example 1 (without dynamic crosslinking agent): The viscosity recovery rate after shearing is 60%, and the viscosity recovery ability is significantly insufficient due to the reliance on a fixed crosslinking network.

[0261] Comparative Example 2 (without thermosensitive monomer): The viscosity recovery rate after shearing is 70%. Although the dynamic crosslinking agent exists, the lack of the structural regulation effect of the thermosensitive monomer leads to a low recovery rate;

[0262] Viscosity change rate;

[0263] The technical solution of the present invention (Example 1): The viscosity change rate is 8.3%, and it shows a high viscosity stability in a high temperature environment of 120° C., which is due to the synergistic effect of the dynamic cross-linking agent and the temperature-sensitive monomer.

[0264] Comparative Example 1 (without dynamic crosslinking agent): The viscosity change rate is 15%, there is a lack of dynamic crosslinking structure, and the molecular chain is prone to degradation at high temperature.

[0265] Comparative Example 2 (without temperature-sensitive monomer): The viscosity change rate was 20%. The temperature-sensitive monomer was not used to adjust the molecular chain structure to adapt to the high temperature environment, and the stability was significantly reduced.

[0266] Phase separation time;

[0267] Technical solution of the present invention (Example 1): The phase separation time is >48h, and the introduction of the dynamic cross-linking agent and the temperature-sensitive monomer enhances the internal stability of the emulsion, and it can remain stable even in a high temperature and high salt environment;

[0268] Comparative Example 1 (without dynamic crosslinking agent): the phase separation time is <24h, lacking the stabilizing effect of the dynamic crosslinking agent, and the emulsion is easy to phase separate at high temperature;

[0269] Comparative Example 2 (without thermosensitive monomer): the phase separation time is <24 h. Due to the lack of the ability of thermosensitive monomer to regulate the adaptability of the molecular network, the phase separation time of the emulsion is relatively short.

[0270] The present invention, through the synergistic effect of the dynamic crosslinking agent and the temperature-sensitive monomer, is significantly superior to the comparative solution lacking innovative ingredients in key performance indicators such as shear loss rate, viscosity recovery rate, viscosity change rate, emulsion particle size uniformity and phase separation time. The present invention solves the problem of insufficient stability and adaptability of the thickener in the prior art in high temperature, high shear and complex downhole environments.

[0271] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a high-performance fracturing fluid emulsion thickener, characterized in that: The steps include: S1. Mix 30% to 50% of the oil phase and 50% to 70% of the emulsifier evenly; S2, preparing an aqueous phase: dissolving the monomer and the cross-linking agent in water, and adjusting the pH to prepare an aqueous phase; S3, emulsification: adding the water phase dropwise into the oil phase to form an inverse emulsion through high-speed shearing; S4, polymerization reaction: adding initiator under nitrogen protection, and carrying out polymerization reaction at 50°C to 70°C; S5, cross-linking treatment: adding a dynamic cross-linking agent in the late stage of polymerization to form a dynamic cross-linking network structure; S6. Post-processing: Through separation, purification and homogenization, an emulsion thickener product is obtained.

2. A process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The oil phase in step S1 includes but is not limited to mineral oil and vegetable oil.

3. The process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The emulsifier in step S1 includes a bifunctional emulsifier and a temperature-sensitive emulsifier; The bifunctional emulsifier is aminopropyl polydimethylsiloxane, which accounts for 70% to 80% of the total mass of the emulsifier; The temperature-sensitive emulsifier is a poly-N-isopropylacrylamide modified surfactant, which accounts for 20% to 30% of the total mass of the emulsifier; The bifunctional emulsifier accounts for 70% to 80% of the total mass of the emulsifier; The temperature-sensitive emulsifier accounts for 20% to 30% of the total mass of the emulsifier.

4. The process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The preparation of the aqueous phase in step S2 specifically includes: S2.1, dissolve the monomer in deionized water, the total monomer concentration is 20% to 25%; S2.2, adding 0.05% to 0.1% of N,N'-methylenebisacrylamide as a basic crosslinking agent, and adding 0.05% to 0.2% of a thiol-containing compound as a dynamic crosslinking agent; S2.3, after uniform mixing by stirring, adjust the pH value of the solution to 7.5-8 using a pH adjuster; S2.

4. Use a homogenizer to stir at a speed of 3000RPM to 5000RPM for 3min to 5min to form a uniform aqueous solution.

5. A process for preparing a high performance fracturing fluid emulsion thickener according to claim 4, characterized in that: The monomers include: 50% to 60% acrylamide, 15% to 20% cationic monomer, 5% to 10% hydrophobic monomer and 10% to 15% thermosensitive monomer.

6. The process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The emulsification in step S3 specifically includes: S3.1, add the aqueous phase solution to the oil phase dropwise at a constant rate to ensure a uniform oil-water ratio and control the drop rate to avoid agglomeration of the aqueous phase; S3.2, under the action of high-speed shearing equipment, at a speed of 3000RPM to 5000RPM, the time is controlled within 15min to 30min, so that the particle size of the formed emulsion is uniform and stable, and the particle size range is controlled within 10μm to 50μm; S3.

3. During the emulsification process, maintain the system temperature at 20℃~30℃ to prevent the emulsifier performance from being affected by temperature fluctuations and ensure the stability of the emulsion.

7. The process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The polymerization reaction in step S4 specifically includes: S4.1, initial polymerization stage: the prepared inverse emulsion is placed in a polymerization reactor, nitrogen is introduced to remove oxygen, the gas flow rate is controlled at 0.5L / min to 1.0L / min, the ventilation time is 10min to 30min, and then the temperature is raised to 50℃ to 55℃; S4.2, add redox initiator, the oxidant is ammonium persulfate, the reducing agent is sodium bisulfite, the mass ratio of oxidant to reducing agent is 1:1.2, and the amount of initiator is 0.5% to 1% of the total weight of the monomer S4.3, the initial polymerization temperature is controlled at 50℃~55℃, the reaction time is 1h~2h, after the emulsion gradually thickens, slowly raise the temperature to 60℃~70℃, and keep the reaction time for 2h~4h until the viscosity reaches the target value; S4.4, after the reaction has been going on for 2h to 3h, add the nanocapsule-coated initiator, the capsule particle size is 200nm to 500nm, and the controlled release time is 1h to 2h, to optimize the monomer polymerization rate and molecular weight distribution; S4.

5. After the reaction is completed, the system is naturally cooled to room temperature, and stirring is stopped to obtain a polymer emulsion thickener.

8. The process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The cross-linking treatment in step S5 specifically includes: S5.

1. After the polymerization reaction has been carried out for 3 to 4 hours, the dynamic crosslinking agent is dissolved in deionized water, and the concentration of the solution is controlled at 0.5% to 1.5%; S5.2, slowly adding the dynamic crosslinking agent solution into the polymerization system, the dynamic crosslinking agent accounting for 0.05% to 0.2% of the total weight of the monomer; S5.

3. After the dynamic cross-linking agent and the polymerization system are uniformly mixed, stirring is continued for 30 min to 60 min, the stirring speed is controlled at 20 rpm to 500 rpm, and the reaction temperature is maintained at 50°C to 70°C.

9. A process for preparing a high performance fracturing fluid emulsion thickener according to claim 8, characterized in that: The dynamic cross-linking agent includes but is not limited to thiol-containing compounds and disulfide compounds.

10. The process for preparing a high-performance fracturing fluid emulsion thickener according to claim 1, characterized in that: The post-processing in step S6 specifically includes: S6.1, using centrifugal separation, the centrifugal speed is 3000RPM ~ 5000RPM, the time is 10min ~ 30min, to remove unreacted monomers and impurities; S6.2, washing the emulsion 2 to 4 times with deionized water, with the ratio of washing volume to emulsion mass being 2:1, to ensure the removal of water-soluble impurities, and purifying the emulsion by a microfiltration device with a filtration pore size of 1 μm to 5 μm to control the particle size distribution of the emulsion; S6.3, use high-pressure homogenization equipment for homogenization treatment, the homogenization pressure is controlled at 20MPa ~ 30MPa, the homogenization time is 10min ~ 20min, ensure that the uniformity of the emulsion particle size is within the range of 10μm ~ 50μm, add antioxidant to stabilize the product, and the amount of antioxidant added is 0.1% ~ 0.3% of the total mass of the emulsion; S6.

4. Adjust the treated emulsion to a solid content of 30% to 50%, and finally store the emulsion thickener in a sealed container and keep it at 15°C to 30°C away from light.

Citation Information

Cited By

  • Amphiphobic nano material for carbonate reservoir, amphiphobic acid solution instant thickening agent and preparation method and application of amphiphobic nano material and amphiphobic acid solution instant thickening agent

    CN120699610A

  • Polymer suspension emulsion for fracturing fluid and preparation method thereof

    CN121064822A